Band offsets of ITO/amorphous GaOx heterojunction determined by x-ray photoemission spectra. (23rd February 2023) - Zhang, Junlin; Yuan, Yidie; Yang, Xiutao; Zheng, Yujie; Zhang, Hongguo; Zeng, Guanggen
Abstract: The band offsets of heterojunctions formed between indium tin oxide (ITO) and amorphous gallium oxide (a-GaO x ) of different stoichiometric ratios were measured by x-ray photoelectron spectroscopy using the Kraut method. a-GaO x films with different stoichiometric ratios were deposited on commercial ITO/quartz substrates using radio frequency magnetron sputtering by varying the Ar/O2 flux ratio. With the increase of oxygen flux in the reaction gas, the oxygen vacancy (VO ) concentration of a-GaO x decreases and its bandgap increases from 5.2 eV to 5.32 eV, while the valence band offset of ITO/a-GaO x heterojunction changes from 0.29 ± 0.07 eV to −0.74 ± 0.06 eV and conduction band offset changes from 0.95 ± 0.085 to 2.10 ± 0.075 eV. The results indicate that the band alignment of ITO/a-GaO x heterojunction can change from type I to type II with the variation of Ga/O stoichiometric ratio, which can provide guidance for the design of their corresponding high-performance heterostructured devices.